(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
The concept of reduplication has attracted interest from many linguists in recent years. This is because reduplication is an important phenomenon in languages. Although some linguists have tried to look at reduplication in Sesotho, its role and function in this language has been neglected. This paper looks at the usage of reduplication and its role in the enrichment of Sesotho. The paper reveals that Sesotho makes use of partial and complete reduplication with various functions such as: showing plurality, emphasis, diminutives, echoic expressions, completeness, originality, intensity, frequency, among others. Another interesting fact in this paper is that Sesotho, like English (Ghomeshi et al., 2004, p. 308) has contrastive reduplication where some speakers use it to contrast one concept from others. In addition, the paper reveals that reduplication in Sesotho can be categorized into prototypical meaning, literal meaning, intensifi ed meaning and value-added meaning.